Dynamic interdependence of advice seeking, loaning, and recovery characteristics in recovery homes. Issue 5 (4th July 2022) - Jason, Leonard A.; Lynch, Gabrielle; Bobak, Ted; Light, John M.; Doogan, Nathan J.
ABSTRACT: Recovery homes in the US provide stable housing for over 250, 000 individuals with past histories of homelessness, psychiatric comorbidity and criminal justice involvement. We need to know more about how these settings help those who remain in recovery. Our study measured advice seeking and willingness-to-loan relationships, and operationalized them as a dynamic multiplex social network—multiple, simultaneous interdependent relationships—that exist within 42 Oxford House recovery homes over time. By pooling relationship dynamics across recovery houses, a Stochastic Actor-Oriented Modeling (SAOM) framework was used to estimate a set of parameters governing the evolution of the network and the recovery attributes of the nodes simultaneously. Findings indicated that advice and loan relationships and recovery-related attitudes were endogenously interdependent, and these results were affected exogenously by gender, ethnicity, and reason for leaving the recovery houses. Prior findings had indicated that higher advice seeking in recovery houses was related to higher levels of stress with more negative outcomes. However, the current study found that recovery is enhanced over time if advice was sought from residents with higher recovery scores. Our study shows that social embedding, i.e., one's position in relationship networks affects recovery prospects. More specifically, the formation of ties with relatively more recovered residents is an important predictor of better outcomes.